Fine Mapping of a Gene (ER4.1) that Causes Epidermal Reticulation of Tomato Fruit and Characterization of the Associated Transcriptome - Cui, Lipeng; Qiu, Zhengkun; Wang, Zhirong; Gao, Jianchang; Guo, Yanmei; Huang, Zejun; Du, Yongchen; Wang, Xiaoxuan (Frontiers in Plant Science, 2017)
The hydrophobic cuticle that covering the surface of tomato (Solanum lycopersicum) fruit plays key roles in development and protection against biotic and abiotic stresses, including water loss, mechanical damage, UV radiation and pathogens and pests. However, genes and regulatory mechanisms involved in cuticle biosynthesis in fleshy fruit are not well understood. In this study, we describe a novel tomato fruit phenotype, characterized by epidermal reticulation (ER) of green fruit and a higher water loss rate than wild type (WT) fruit. The ER phenotype is controlled by a single gene, ER4.1, derived from an introgressed chromosomal segment from the wild tomato species S. pennellii (LA0716). We performed fine mapping of the single dominant gene to an ~300 kb region and, based on comparative RNA-seq analysis of ER and WT fruit peels, Solyc04g082540, Solyc04g082950, Solyc04g082630 and Solyc04g082910 were found to be potential candidate genes for the ER4.1 locus. In addition, the transcriptome analysis revealed that the expression levels of genes involved in cutin, wax and flavonoid biosynthesis were altered in the ER fruit compared with WT. This study provides new insights into the regulatory mechanisms and metabolism of the fruit cuticle.